Proceedings of the 15th Conference on Computational Linguistics - 1994
DOI: 10.3115/991250.991324
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing text genres with simple metrics using discriminant analysis

Abstract: A simple method for categorizing texts into pre-determined text genre categories using the statistical standard technique of discriminant analysis is demonstrated with application to the Brown corpus. Discriminant analysis makes it possible use a large number of parameters that may be specific for a certain corpus or information stream, and combine them into a small number of functions, with the parameters weighted on basis of how useful they are for discriminating text genres. An application to information re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(132 citation statements)
references
References 8 publications
0
127
0
5
Order By: Relevance
“…Many studies since that of Mosteller and Wallace have shown the efficacy of function words for authorship attribution in different scenarios (Morton 1978;Burrows 1987;Karlgren & Cutting 1994;Merriam & Matthews 1994;Kessler et al 1997;Argamon et al 1998;Holmes 1998;de Vel et al 2001;Holmes et al 2001aHolmes et al , 2001bBaayen et al 2002;Binongo 2003;Juola & Baayen 2003;Zhao & Zobel 2005;Argamon & Levitan 2005;Koppel et al 2005Koppel et al , 2006a, confirming the hypothesis that different authors tend to have different characteristic patterns of function word use.…”
Section: Function Wordsmentioning
confidence: 50%
“…Many studies since that of Mosteller and Wallace have shown the efficacy of function words for authorship attribution in different scenarios (Morton 1978;Burrows 1987;Karlgren & Cutting 1994;Merriam & Matthews 1994;Kessler et al 1997;Argamon et al 1998;Holmes 1998;de Vel et al 2001;Holmes et al 2001aHolmes et al , 2001bBaayen et al 2002;Binongo 2003;Juola & Baayen 2003;Zhao & Zobel 2005;Argamon & Levitan 2005;Koppel et al 2005Koppel et al , 2006a, confirming the hypothesis that different authors tend to have different characteristic patterns of function word use.…”
Section: Function Wordsmentioning
confidence: 50%
“…We wanted to investigate whether the sort of NEs in a given text might be a discriminating feature for classifying genre [20]. Preliminary results on this subject have already been published in [1].…”
Section: Context and Motivationmentioning
confidence: 99%
“…Karlgren [4,6,7] has done several experiments in genre classification. In [4] he shows that the texts that were judged relevant to a set of TREC queries differ systematically (in terms of style) from the texts that were not relevant.…”
Section: Related Workmentioning
confidence: 99%